Opłata za czynności związane z certyfikacją w zakresie ochrony danych osobowych - Antonów, Dobrosława (Uniwersytet Wrocławski. Wydział Prawa, Administracji i Ekonomii, 2018)
On 25 May 2018, the Regulation (EU) 2016/679 of the European Parliament of the Council of 27 April 2016 on the protection of natural persons in connection with processing of personal data and on the free movement of such data and repealing Directive 95/46/EC (General Data Protection Regulation) (hereafter GDPR), and the Act of 10 May 2018 on protection of personal data came into force. The European system of personal data protection predicts the procedure of certifying showing conformity of personal data processing operation whit GDPR. The certifying on the basis of Polish Act is payed. The fee for activities connected with certifying by the President of Department of Personal Data Protection is the Budget income. This fee issues are described in the Article. Its construction and features are described in the Article. The author tries to assess its legal character. Fundamental consideration is focused on the issue of the fee and putting it in wider context of public fees issue in Poland
Keywords: fee; certification; personal data protection